2018
DOI: 10.2174/1389200218666170912161449
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutics and Immunoprophylaxis Against Noroviruses and Rotaviruses: The Past, Present, and Future

Abstract: Background: Noroviruses and rotaviruses are important viral etiologies of severe gastroenteritis. Noroviruses are the primary cause of nonbacterial diarrheal outbreaks in humans, whilst rotaviruses are a major cause of childhood diarrhea. Although both enteric pathogens substantially impact human health and economies, there are no approved drugs against noroviruses and rotaviruses so far. On the other hand, whilst the currently licensed rotavirus vaccines have been successfully implemented in over 100 countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 292 publications
(380 reference statements)
0
14
0
3
Order By: Relevance
“…In addition to the effect on individual health, the worldwide economic burden of norovirus disease is estimated to be approximately 60 billion dollars per year [5]. As the understanding of the prevalence and burden of norovirus disease strengthens, the need for preventative and therapeutic measures becomes more apparent, including the development of an effective vaccine [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the effect on individual health, the worldwide economic burden of norovirus disease is estimated to be approximately 60 billion dollars per year [5]. As the understanding of the prevalence and burden of norovirus disease strengthens, the need for preventative and therapeutic measures becomes more apparent, including the development of an effective vaccine [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, research on therapeutic drugs against DWV is still rare. Egg yolk antibodies known as immunoglobulin Y (IgY) have been widely utilized in the prevention and control of epidemic diseases associated with Acinetobacter baumannii, Vibrio splendidus, the Dengue virus, noroviruses, rotaviruses and duck adenovirus 3 (Fink et al, 2017;Ghosh, Malik & Kobayashi, 2017;Jahangiri et al, 2019;Li et al, 2016;Yin et al, 2019). Moreover, Sun et al (2018) reported that specific IgY could be obtained from hens immunized with an inactivated Chinese Sacbrood virus (CSBV) vaccine, which has the ability to neutralize CSBV.…”
Section: Discussionmentioning
confidence: 99%
“…Some have been designed to block the entry of viruses into the host cells by targeting the viral envelope proteins, while others target essential intracellular viral proteins (Wu et al., 2017). These agents have shown a particular promise against rotavirus and norovirus (Ghosh et al., 2018), the most common causes of severe acute gastroenteritis in children (Riera-Montes et al., 2017). Several VHH generated against Group A rotavirus (RVA) strains were shown to neutralize rotavirus in vitro and provided different degrees of in vivo passive protection against rotavirus challenge when orally administered in a neonatal mouse model (van der Vaart et al., 2006; Garaicoechea et al., 2008; Gómez-Sebastián et al., 2012; Tokuhara et al., 2013; Maffey et al., 2015).…”
Section: Vhh Antibody Fragmentsmentioning
confidence: 99%